The Effect of Warm Ginger Compress Toward Pain Level of Arthritis Gout Sufferer in Waimital Village, Kairatu Subdistrict, West of Seram Regency - Risman Tunny; Jayanti Djarami; Yunsi Tambipessy Yunsi Tambipessy (Humanistic Network for Science and Technology (HNST), 2018)
Arthritis gout is an inflammation process due to inflammation on cristal sour tendon in tissue around the joint. The disease engenders many lamentations such as pain of foot, waist, arm neck and other joints. Non pharmacology action for the patients of Arthritis Gout is warm ginger compress. Compress is stand of action by a nurse in order to decrease the pain. The objective of the research is to find out the influence of compress ginger warm toward decrease of pain Arthritis Gout sufferer in Waimital village, Kairatu subdistrict, West of Seram Regency 2016. The kind of research was a pre-experimental design (one group pre-post test design) and the sample was taken using random sampling technique. The data was analyzed using Wilcoxon test. Based on Wilcoxon test it was obtained p-value = 0.000. Thus, H0 was rejected. It means there was a significant correlation between warm ginger compress with the decreasing of Arthritis Gout sufferer in Waimital village, Kairatu subdistrict, West of Seram Regency 2016. Keywords: Pain scale, Warm ginger compress, Gout arthritis